Comparing historic military capabilities: apples with apples - Fisher, Richard (Taylor & Francis, 2024)
Using comparative historical analysis to compare and contrast historic military capabilities is possible using the Defence Lines of Development as a model. Richard Fisher demonstrates how it is not appropriate to merely compare technical aspects of equipment, but that it is necessary to also consider the training, personnel, information, doctrine and concepts, organisation, infrastructure and logistics as part of a comprehensive comparison. Equipment comparisons exist but are flawed as they may not identify the critical factors that enhance or diminish the overall capability. The method is evaluated using the infantry section’s machine guns of the Second World War: the Bren and MG42.